Analysis of the Effect of Attraction, Accessibility (4ASC) Components on Visitor Satisfaction in Tourism Destinations Samosir District - Saydillah Isya Akbar; Robert Sibarani; Charloq (Journal of Social Interactions and Humanities, 2023)
This study aims to determine and analyze the effect of the 4asc attributes (attraction, accessibility on visitor satisfaction at tourist destinations in Samosir Regency. The population in this study were visitors to tourist attractions in 3 sub-districts, namely Harian sub-district, Pangururan sub-district and Simanindo sub-district in Samosir Regency. The sampling technique in this study was non-probability sampling as many as 135 respondents. Methods of data analysis using multiple regression analysis. The results of the study show that Attraction (X1) has an influence on visitor satisfaction. Accessibility (X2), has an influence on visitor satisfaction.